2015
DOI: 10.11648/j.ijmsa.s.2015040201.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano Silica on the Mechanical Properties of Styrene-Butadiene Rubber (SBR) Composite

Abstract: Abstract:The aim of this research is to study the effect of nano silica which use as a filler with loading level (0.1, 0.3, 0.5, 1, 3, 5, 10, 20, 30, 40 pphr) on mechanical properties of SBR such as Tensile strength, elastic modulus, hardness, abrasion, fatigue and tear resistance. The results show that on addition of small quantities of nano silica an increase of mechanical properties occurs. While at high percent of nano silica aggregation in rubber matrix occurs and decrease themechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Therefore, according to this test, the nanocomposite with 3 phr nanofiller is the acceptable option. This finding is in accordance with that reported by Ahmed et al 29 The tensile strength in the sample with 5 phr nanofiller decreased to 13.6. The reason is that the nanofiller probably play the double role of reinforcer and the filler at this amount.…”
Section: Mechanical Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, according to this test, the nanocomposite with 3 phr nanofiller is the acceptable option. This finding is in accordance with that reported by Ahmed et al 29 The tensile strength in the sample with 5 phr nanofiller decreased to 13.6. The reason is that the nanofiller probably play the double role of reinforcer and the filler at this amount.…”
Section: Mechanical Propertiessupporting
confidence: 93%
“…They studied mechanical properties of nanocomposites and observed that tensile properties, loss modulus and loss tangent of the nanocomposite improved significantly. Jaleel Kareem et al 29 studied the effect of nano silica as a filler with loading level (i.e., 0.1, 0.3, 0.5, 1, 3, 5, 10, 20, 30, and 40 parts of filler per hundred parts of rubber (phr)) on mechanical properties of styrene-butadiene rubber (SBR). Their results showed that small quantities of silica nanoparticles improved the mechanical properties better than high quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, to our knowledge, there is no direct link between various dispersion states and final mechanical properties of composites while the interest of this dispersion was highlighted in various studies. Indeed, it is proven that the fillers agglomeration in the matrix causes premature failure of the composite [18][19][20] and lead, in some cases to decrease the composites Young's modulus [21]. Usually, most of the composites are a mix of isolated and agglomerated particles.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 shows the effect of nano silica level on abrasion loss, it increases by increasing of nano silica level. Thus, abrasion resistance decreases due to the agglomeration of silica nanoparticles but 1 phr of silica nanoparticles gives the best abrasion resistance with the lowest abrasion loss (Ahmed et al, 2015). Figure 7 shows the effect of nano silica level on compression, it decreases by increasing nano silica level down to 3 phr and increases after that.…”
Section: Resultsmentioning
confidence: 98%
“…Nano silica is added to rubber as a unique filler or added with carbon black as dual filler. Many studies include the addition of nano silica with small amounts (<4% of the total weight of rubber compound) to avoid the agglomeration of silica particles (Rajkumar et al, 2013;Abitha and Vasudev, 2014;Ahmed et al, 2015;Sultani et al, 2017). Acid resistance of rubber composites can be determined by the following equation (ASTM, 1998):…”
Section: Introductionmentioning
confidence: 99%